The Strategic Role of Internal Audit in Strengthening Good University Governance - Betty Betty; Lucyani Meldawati; Mustamin Mustamin; Erwinsyah Erwinsyah; Natalin Vira (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Good University Governance (GUG) is an essential concept for fulfilling the goals of higher education institutions. Universities can effectively support this by implementing the five principles of GUG, aided by organizational units like the Internal Control Unit (Satuan Pengawas Internal/SPI) within the institution. This study seeks to analyze the influence of the Internal Control Unit on the implementation of Good University Governance at Tadulako University. Using a quantitative method, the research was conducted at Tadulako University in Palu, with data gathered from 57 respondents selected through incidental sampling. The research tools were verified for validity and reliability. Data analysis utilized descriptive statistics and simple regression analysis. Results show that the Internal Control Unit has a positive effect on Good University Governance. Therefore, it is crucial for all stakeholders to acknowledge the Internal Control Unit’s role to strengthen its impact on effective university governance.